1996
DOI: 10.1111/j.2042-3306.1996.tb03096.x
|View full text |Cite
|
Sign up to set email alerts
|

Character and duration of pharmacological effects of intravenous isoxsuprine

Abstract: Summary Isoxsuprine is a therapeutic medication used to treat navicular disease and other lower limb problems in horses and is one of the more frequently detected therapeutic agents in racing horses. In a crossover study, horses were administered isoxsuprine i.v. to determine the character and duration of its pharmacological effects. Isoxsuprine significantly increased heart rate 5–150 min following injection. Unrestrained activity following isoxsuprine treatment was significantly greater than control activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…It was beyond the scope of this trial to evaluate these parameters, but they most certainly would have been in between to those reported by Matthews et al. (1986) and Harkins et al. (1996).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…It was beyond the scope of this trial to evaluate these parameters, but they most certainly would have been in between to those reported by Matthews et al. (1986) and Harkins et al. (1996).…”
Section: Discussionmentioning
confidence: 71%
“…The biological activity of the resulting metabolites – isoxsuprine‐glucuronide and isoxsuprine‐glucuronide‐dipotassium (Bosken et al., 2000) – has not been evaluated, but it is highly likely that their effects might be insignificant, at least cardiovascularly. This is because intravenous, but not oral, administration of isoxsuprine produces a transient decrease in systemic blood pressure, systemic vascular resistance and stroke volume, as well as a transit increase in heart rate and cardiac output (Matthews et al., 1986; Harkins et al., 1996, 1998). It was beyond the scope of this trial to evaluate these parameters, but they most certainly would have been in between to those reported by Matthews et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoxsuprine is predominantly a β 2 agonist but has also been described as an α‐receptor antagonist, thereby explaining its peripheral vasodilatatory effect 111 . However, this is in contrast to the findings of Harkins and Tobin, 110 who demonstrated that isoxsuprine given orally had little effect on heart rate, sweat output, or vascular tone, whereas intravenous administration caused an increase in heart rate, cutaneous blood flow, sweat output and vascular tone, but that these effects were short lived. This finding is supported by another study, which showed that isoxsuprine given orally had no effect on sweating 112 …”
Section: Control Of Sweatingmentioning
confidence: 90%
“…The onset of sweating correlates with cutaneous blood flow. Intravenous injection of isoxsuprine, a vasodilator drug used in horses for lower limb problems, produces an increase in sweat production and cutaneous blood flow to the pastern, whereas controls produce neither 110 . Isoxsuprine is predominantly a β 2 agonist but has also been described as an α‐receptor antagonist, thereby explaining its peripheral vasodilatatory effect 111 .…”
Section: Control Of Sweatingmentioning
confidence: 99%